2014
DOI: 10.1590/s0102-05362014000300010
|View full text |Cite
|
Sign up to set email alerts
|

Resistência de porta-enxertos de cucurbitáceas a nematóides e compatibilidade da enxertia em melão

Abstract: Resistance of cucurbita rootstocks to nematodes and compatibility of grafting with net melonNematodes severely attack net melon plants under protected cultivation conditions. The objective of this research was to select rootstocks with resistance to Meloidogyne incognita and M. javanica. and musk cucumber (Sicana odorifera). To evaluate the resistance, seedlings were transplanted to pots and the root inoculated with 3,000 eggs and second stage juveniles of M. incognita and M. javanica. Fifty days after the ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…However, the authors state that these measures are laborious, burdensome and often inefficient. The use of resistant plants, therefore, is the most economical and efficient method to control root-knot nematodes in cucurbits, including muskmelon crops (Ito et al 2014).…”
Section: Key-wordsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the authors state that these measures are laborious, burdensome and often inefficient. The use of resistant plants, therefore, is the most economical and efficient method to control root-knot nematodes in cucurbits, including muskmelon crops (Ito et al 2014).…”
Section: Key-wordsmentioning
confidence: 99%
“…Santos et al (1999) studied the resistance of muskmelon genotypes to M. incognita and observed that 2 of the 54 genotypes assessed exhibited resistance to the pathogen. Ito et al (2014) evaluated sources of cucurbit resistance to M. incognita and M. javanica and found that the 'Gaúcho Redondo' genotype was resistant to M. javanica. However, none of the genotypes is resistant to both species.…”
Section: Key-wordsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of resistance to M. incognita in the 'Gaúcho Redondo' cultivar, carried out by ITO et al (2014), facilitated the study of inheritance for the trait in question. According to CRUZ & REGAZZI (1994), a genetic control study with generations F 1 , F 2 and backcrosses, including parental P 1 and P 2 , can lead to the quantification of the magnitude and nature of genetic variability in the segregating population and the assessment of the relative importance of genetic effects, which compose the averages of the studied populations.…”
Section: Introductionmentioning
confidence: 99%
“…showed resistance for both root-knot species (Pinheiro and Amaro, 2010;Ferraz et al, 2012;Diniz et al, 2016a;Diniz et al, 2016b). Furthermore, there are some efforts to understand Cucumis metuliferus (E. Mey) resistance mechanism against root-knot nematode and use it for breeding programs (Ling et al, 2017;Ito et al, 2014;Pinheiro and Amaro, 2010). It is relevant to mention that most chemical nematicides have been removed from the market, mainly due to the environmental contamination risks and high toxicity of compounds to human health (Kerry, 1992).…”
Section: Introductionmentioning
confidence: 99%